Uji Efek Tonikum Ekstrak Etanol Kombinasi Temu Putih (Curcuma zedoaria) dan Temu Hitam (Curcuma aeruginosa) terhadap Mencit Putih Jantan (Mus musculus) - Afina Rachmalia Artha Aryasuta; Niken Luthfiyanti; Kharisma Jayak Pratama (Pusat riset dan Inovasi Nasional, 2025)
Tonic is a preparation thats can stqrengsthen the body and improve stamina. Curcuma zedoaria and Curcuma aeruginosa are known to have phytochemical compunds such as flavonoids, alkaloids, saponins, tannin, triterpenoids, curcuminoid and polyphenols that can function as stimulant and tonics. This studiy aimed to investigate tonic effects of ethanolic extracts of Curcuma zedoaria, ethanolic extract of Curcuma aeruginosa, and their combinations on male white mice (Mus musculus). Curcuma zedoaria rhizome and Curcuma aeruginosa rhizome were extracted using the maceration method for 3 days using 70% ethanol solvent which was then thickened in a waterbath. A total of 35 male mice were divided into 7 groups with different treatments, including negative control (aquadest), positive control (caffeine 100 mg/kgBB), ethanolic exctract of Curcuma zedoaria (600 mg/kgBB), ethanolic extract of Curcuma aeruginosa (600 mg/kgBB), and combination ethanolic extract of Curcuma zedoaria and Curcuma aeruginosa at dosage of 150:450 mg/kgBB, 300:300 mg/kgBB, and 450:150 mg/kgBB. Tonic effect were evaluated using natatory exhaustion and rotarod tests. The natatory exhaustion test is carried out by observing how long the mice swim, while the rotarod test is carried out by observing how long the mice stay on the rotarod apparatus. The data analyzed using ANOVA and Tukey’s test. The results of One Way Anova showed a there were significansts differensce in each groups (p<0,05) with combination of Curcuma zedoaria : Curcuma aeruginosa (150:450 mg/kgBB) yielding the best tonic effect. From the result of Tukey’s followsup test, it showed that the highers the dosae of Curcuma aeruginosa rhizome extracts the better the tonics effects giiven. This suggest that Curcuma aeruginosa has a dominant role in enhancing phsycal endurance in male white mice.